Analysis Of The Effect Of Murabahah Product Pricing On The Number Of Microfinance Customers (A Study At Sharia People’s Financing Bank Serambi Mekah, Langsa) - Pasaribu, Rifdah Atika; Nasution, Juliana; Inayah, Nurul (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of Murabahah product pricing on the number of microfinance customers at BPRS Serambi Mekah Langsa. Using a quantitative descriptive method and Likert-scale questionnaires, 100 respondents were surveyed from a population of 400. The results, processed via SPSS 25, indicate that pricing has a positive and significant effect on customer numbers. These findings suggest that competitive pricing strategies can increase customer interest, especially in Islamic microfinance sectors. This highlights the importance of proper pricing policies to attract and retain customers in Sharia-based banking institutions.